ChemInform Abstract: Non‐Rare‐Earth BaMgAl10‐2xO17:xMn4+, xMg2+: A Narrow‐Band Red Phosphor for Use as a High‐Power Warm w‐LED. Issue 31 (14th July 2016) - Wang, Bo; Lin, Hang; Huang, Feng; Xu, Ju; Chen, Hui; Lin, Zebin; Wang, Yuansheng
Abstract: BaMgAl10‐2x O17 :xMn 4+, xMg 2+ (x = 0.005—0.05) samples are prepared by firing and sintering stoichiometric amounts of BaCO3, MgO, Al2 O3, and MnCO3 in air (1.